Чинники формування конкурентоспроможності підприємств-виробників будівельних матеріалів - Слюсаренко, О. Ю. (НТУ "ХПІ", 2015)
У статті розглянуті проблеми розвитку галузі будівельних матеріалів, надається коротка характеристика сучасного стану вітчизняного будівельного комплексу, визначені головні чинники конкурентоспроможності підприємств-виробників будівельних матеріалів, від яких залежить розвиток підприємств даної галузі, також запропоновані показники для оцінки рівня конкурентоспроможності підприємства-виробника будівельних матеріалів.

In the article the problems of building materials, provided a brief description of the current state of the domestic construction industry, identified the main factors of competitiveness of manufacturers of building materials that affect the development of enterprises in the industry, as proposed indicators to measure the competitiveness of the manufacturer of building materials. Found that competitiveness depends on the effectiveness of management, and, above all, strategic planning. Evaluation of competitiveness is the basis for developing competitive strategies to create or enhance competitive advantage that will determine the success of the company in the long run. The problem of increasing the competitiveness of domestic producers of building materials is relevant in the present conditions, characterized by a decrease in effective demand and decline in construction. The choice of effective competition policies should be based on a comprehensive evaluation of enterprise competitiveness, taking into account the specifics of the industry.
Factors of formation of competitiveness of manufacturers of building materials
Keywords: ринкова економіка; вітчизняні підприємства; виробництво; промисловість; competitiveness; production of construction materials; factors of competitiveness; completion policy